2018
DOI: 10.1016/j.ebiom.2018.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Association of immune response with efficacy and safety outcomes in adults with phenylketonuria administered pegvaliase in phase 3 clinical trials

Abstract: BackgroundThis study assessed the immunogenicity of pegvaliase (recombinant Anabaena variabilis phenylalanine [Phe] ammonia lyase [PAL] conjugated with polyethylene glycol [PEG]) treatment in adults with phenylketonuria (PKU) and its impact on safety and efficacy.MethodsImmunogenicity was assessed during induction, upward titration, and maintenance dosing regimens in adults with PKU (n = 261). Total antidrug antibodies (ADA), neutralizing antibodies, immunoglobulin (Ig) M and IgG antibodies against PAL and PEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 27 publications
1
73
0
Order By: Relevance
“…The administered enzyme is a pegylated recombinant Anabaema variabilis phenylalanine ammonia lyase (PAL) to be administered daily. About 60% of treated patients in a phase III clinical trial achieved blood Phe ≤ 360 µM, but adverse reactions and anaphylaxis were associated with this therapy [41]. To overcome these limitations, a RBC-mediated delivery of PAL was investigated in a validated murine model of PKU [42,43].…”
Section: Rbcs For the Delivery Of Phenylalanine Ammonia Lyasementioning
confidence: 99%
“…The administered enzyme is a pegylated recombinant Anabaema variabilis phenylalanine ammonia lyase (PAL) to be administered daily. About 60% of treated patients in a phase III clinical trial achieved blood Phe ≤ 360 µM, but adverse reactions and anaphylaxis were associated with this therapy [41]. To overcome these limitations, a RBC-mediated delivery of PAL was investigated in a validated murine model of PKU [42,43].…”
Section: Rbcs For the Delivery Of Phenylalanine Ammonia Lyasementioning
confidence: 99%
“…8 These abnormalities can include lower IQ, executive functioning deficits, and psychiatric disorders (anxiety and depression), with the incidence of deficits increasing with increased blood Phe concentration. [10][11][12] A recent US Food and Drug Administration (FDA)-approved enzyme substitution therapy (pegvaliase) for adults with uncontrolled hyperphenylalaninemia on a diet has revealed dramatic improvements in blood Phe management [13][14][15][16] but is associated with a significant incidence of immune-mediated hypersensitivity reactions against the foreign protein. Additionally, pegvaliase is not approved for use in individuals less than 18 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, PEGylation is a commonly used strategy to extend in vivo duration of action of therapeutics protein by reducing its immunogenicity and protecting it from the inactivation by anti-drug antibodies. However, many clinical studies have demonstrated that in some cases patients can also develop anti-PEG antibodies which caused adverse reactions and anaphylaxis (Hershfield et al, 2014;Gupta et al, 2018). Differently, by delivering the therapeutic enzymes through RBCs, PEGylation step can be avoided since the foreign enzyme is confined inside the erythrocytes, allowing it to be hidden from the immunological system and thus from any neutralizing antibodies that may be present in circulation.…”
Section: Discussionmentioning
confidence: 99%